Strategies for Applying AI in Vocational Education and Training. Predict: Preliminary Results and Impact - Potes Barbas, Maria; Teles Vieira, Andreia; Duarte Branco, Paulo; Casimiro, Elsa (Calitatea Vieții, 2025)
This paper intends to demonstrate and analyze strategies for applying AI in vocational education and training. In particular, it analyzes the preliminary results and their implications of the PREDICT: JOBS OF THE FUTURE WITH AI 4 VET INCLUSION project. The PREDICT project addresses the pressing challenges faced by the emerging workforce, particularly those graduating from vocational education and training (VET) programs. By formulating comprehensive strategies, the project aims to promote the inclusiveness, lifelong learning and mentoring that are critical to the career advancement of these individuals, especially those from disadvantaged backgrounds. Through a series of objectives, including developing a holistic digital reskilling model, addressing digital illiteracy, creating mentorship guidelines, promoting green digital tools, and establishing sustainable models, PREDICT seeks to equip VET students and other target groups with the necessary skills and readiness for the digital age. Ultimately, the project aims to empower individuals with digital resilience and readiness tailored to their individual needs, ensuring their successful integration into the evolving workforce landscape. In this paper, we analyze the preliminary results, such as the manuals on green digital tools for innovative jobs and the IA course prototype, and their impact on the overall project. The impact is one of the most important indicators because the goal of this project is to create roadmaps, guidelines, blueprints, and other mechanisms that can be easily replicated or used by any of our European peers (be it an NGO, a company, an association or even a country).